THE ROLE OF CALCIUM-PERMEABLE KAINATE AND AMPA RECEPTORS IN THE CONTROL OF EXCITATION IN THE HIPPOCAMPAL NEURAL NETWORK (Experimental biology, 2025)
Functional stability of the central nervous system and its resistance to pathological hyperexcitability, including the development of epileptiform activity, critically depend on the mechanism of direct inhibition. For this mechanism to work effectively, GABAergic inhibitory interneurons must be activated and release the mediator earlier than the principal glutamatergic neurons, which requires a specific molecular mechanism for this temporal advantage. A study conducted on oscillating cultures and acute slices of the adult rat hippocampus showed that GABAergic neurons exhibit a fast Ca2+ response, while glutamatergic neurons respond with a delay. It was established that the fast-responding neurons are GABAergic interneurons that express Ca2+-permeable Kainate (CP-KA) and AMPA (CP-AMPA) receptors. These receptors, which lack the GluA2 subunit, function as low-threshold ion channels, allowing GABAergic cells to become excited even with minimal depolarization and generate the Ca2+ signal necessary for the immediate release of GABA. Pharmacological blockade of GABA(A) receptors completely abolished the delay in the excitation of the principal population, confirming that GABA-dependent inhibition is responsible for this effect. Thus, the expression of CP-KA and CP-AMPA receptors represents a key cellular mechanism ensuring the control, delay, and desynchronization of neural network excitation, which is of great importance for understanding the mechanisms of synaptic plasticity and epileptogenesis.
Keywords: mediator, desynchronization, neurons, hippocampus, epileptiform activity, action potential, depolarization, inhibition, homeostasis.